Impact of Training on Employee Performance at Public Finance Management Training Center (PFMTC) - Karkee, Anupama (SADGAMAYA, 2025)
This study investigates the effectiveness of in-service training programs in enhancing individual employee performance within Nepal's public sector. Using a sample of 133 respondents, the research assesses the relationship between training and key performance outcomes such as job-related skills, personal competencies, and professionalism. The findings reveal a significant positive correlation between training effectiveness and improved employee performance. Employees perceive training as instrumental in bridging the gap between their current and desired performance levels. The study emphasizes the need for regular evaluations of training programs to ensure they align with organizational goals and maximize employee potential.